The Study of Common Link Theory of G.H.A Juynboll As a Method of Selecting Authentic Hadith - Mochammad Harun Rosyid (West Science Interdisciplinary Studies, 2023)
The problem of hadith authenticity has become an important problem in hadith studies. Because, a hadith is a manifestation of the words or deeds carried out by the prophet over a long period, even since the time of the companions there have also been attempts to falsify the hadith of the prophet with a variety of different backgrounds. This study uses a qualitative approach to study. The research method used by researchers is qualitative which aims to find out hidden meanings, develop theories, ensure the correctness of data and examine the history of development. Development of the Common Link Theory Juynboll was born in the West which emphasizes the authenticity of hadith from a historical perspective. The analytical method of this theory is based on basic assumptions that have long been developed in the Orientalist scientific tradition. Orientalists study hadith based on a historical approach with conclusions and theories that are relatively different from the theories developed and applied by hadith scholars. Of all the explanations of hadith studies in the orientalism tradition using the common link method, although in many cases it provides several controversial implications, within certain limits it does not rule out its use in the tradition of selecting authentic hadiths.